(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article is devoted to the socio-economic nature of bank security, external and internal threats to the economic security of banking business, economic security indicators of the banking system, the degree of protection of financial interests of banks by the Central Bank, the level of competition in the banking market in the country, the Central Bank analyzed the quality level of regulation and control of banking activities, the level of capitalization of the state banking system, indicators of financial security, including the budget deficit, the stability of the country’s national currency. Also, attention is paid to the reforms implemented by the Central Bank in the Republic of Uzbekistan to improve the economic security of the banking system.